The law of human progress Rede uitgesproken bij de aanvaarding van het ambt van hoogleraar informatierecht aan de Universiteit van Amsterdam op 18 October 2018 - Gervais, Daniel J. 1963- (DeLex, 2019)
In his inaugural lecture Daniel Gervais used an historical perspective to illustrate whether and how the law can contribute to human progress
Inaugural lecture University of Amsterdam 18 October 2018